A study on oil yield differences between clonal and DXP variety oil palm for an ortet selection at Risda Semaian dan Landskap (RSSB), Sungkai, Perak / Farah Hannan Roslee - Roslee, Farah Hannan (Faculty of Plantation and Agrotechnology, 2018)
Oil palm (Elaeis guineensis Jacq.) is one of the major crops that give huge contribution to Malaysian economy. The relatively poor yield of palm oil in commercial and smallholder plantations compared to the proven potential yield of some existing varieties, coupled with the lack of progress in improving this situation over the past decade, has attached much comment in the industry and more widely as the oil palm yields in Malaysia is actually declined between 2008 and 2012. It is significant to study the differences in term of oil yield production between clonal and DxP oil palm to determine which type of planting materials is relevant for the ortet selection in developing high quality of planting materials in future in for commercial planting. The relationship between Fresh Fruit Bunch weight and oil to bunch on oil yield also has been studied to determine the dominant factors that affected the production of oil yield. A study was carried out at Risda Semaian dan Landskap (RSSB), Sungkai, Perak to achieve all the objectives by collecting the secondary data on oil yield as well as the Fresh Fruit Bunch (FFB) weight and the oil to bunch ratio. The weight of FFB tends to influence the amount of oil yield produced for each palm on the two different plots. Palm trees that produced >50kg of oil yield (kg/palm/year) will be used for an ortet selection as specified on the Malaysian Standard (MS 2099:2008).